Pengaruh E-Product Quality, E-Promotion, dan E-Word Of Mouth terhadap E-Buying Decision (Pengguna Shopee Mahasiswa Strata I Fisip Universitas Diponegoro) - Zulfa Rahma; Dinalestari Purbawati; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2023)
This study aims to determine the influence of E-product quality, e-promotion, and e-word of mouth on e-buying decisions. This study used an explanatory research type with a non-probability sampling technique through a purposive sampling approach. The data collection was carried out by distributing research questionnaires to 100 students of the Faculty of Social and Political Sciences, Diponegoro University. E-product quality, e-promotion, and e-word of mouth have a positive effect on e-buying decisions on Shopee consumers, FISIP Diponegoro University students.  E-product qualitys accounted for 20.92% of e-buying decisin, e-ormotion accounted for 41.10%, and e-word of mouth accounted for 35.40% of e-buying decisions. The three variables simultaneously affecting the e-buying decision accounted for 46.20%. So, it is recommended that Shopee Mall can be more flexible about the use of promos offered, increase the speed of product delivery so that it does not exceed the estimated delivery and provide qualifications for sellers to provide more detailed and clear information and be easily accessible to consumers.Penelitian ini bertujuan untuk mengetahui pengaruh E-product quality, e-promotion, dan e-word of mouth terhadap e-buying decision. Penelitian ini menggunakan tipe explanatory research dengan teknik pengambilan sampel non probability sampling melalui pendekatan purposive sampling. Pengumulan data dilakukan dengan menyebarkan kuesioner penelitian pada 100 Mahasiswa Fakultas Ilmu Sosial dan Politik Universitas Diponegoro. E-product quality, e-promotion, dan e-word of mouth berpengaruh positif terhadap e-buying decision pada konsumen Shopee Mahasiswa FISIP Universitas Diponegoro. . E-product quality menyumbang 20,92% terhadap e-buying decisin, e-ormotion menyumbang sebesar 41,10%, dan e-word of mouth menyumbang sebesar 35,40% terhadap e-buying decision. ketiga variabel secara simultan mempengaruhi e-buying decision menyumbang sebesar 46,20%. Maka, disarankan agar Shopee Mall dapat lebih flexible mengenai penggunaan promo yang ditawarkan, meningkatkan kecepatan pengiriman produk agar tidak melebihi estimasi pengiriman dan memberikan kualifikasi bagi seller untuk memberikan informasi lebih detail dan jelas serta mudah diakses konsumen.